The impact of social norms of responsibility on corporate social responsibility short title: the impact of social norms of responsibility on corporate social responsibility - You, Leyuan (Journal of business ethics, 2024)
Social norms of responsibility are shared beliefs on what constitutes responsible behavior, and they play a significant role in determining CSR. This study analyzes how social norms of responsibility permeate corporate boundaries and influence CSR through political leaders, corporate executives, employees, and the public. Socially irresponsible behaviors of the above populations are used as proxies for local social responsibility norms and related to CSR ratings for firms headquartered in the twenty largest U.S. metro areas. The empirical results show that firms headquartered in cities with more responsible social norms exhibit higher ESG scores even after controlling for various demographic, regional, and economic factors. Social responsibility norms encourage firms to be more responsible but are ineffective in deterring irresponsible corporate behaviors. Corporate and political leaders are the essential channels through which social norms of responsibility influence CSR, highlighting the importance of instituting regulations and setting high ethical standards for political and business leaders. This study also demonstrates that social norms have a significant impact on firms with leaders who are more susceptible to local social norms (i.e., local leaders) than non-local leaders. In addition, this study documents a negative bias for responsible social norms in that they condemn irresponsible behaviors more than reward responsible ones. Collectively, the above findings underline the importance of social norms of responsibility in shaping CSR and provide additional insights into societal motivations for CSR.